Distinctive response of thermospheric cooling to ICME and CIR-driven geomagnetic storms - Bag, Tikemani; Rout, Diptiranjan; Ogawa, Y.; Singh, Vir (Frontiers in Astronomy and Space Sciences, 2023)
The temporal response of thermospheric CO2 and NO cooling emissions is investigated during ICME and CIR-driven geomagnetic storms by using data from the SABER instrument onboard the TIMED, GRACE and DMSP satellites. The superposed epoch analysis reveals that the cooling emissions experience a strong enhancement and quick recovery to pre-event value within 3-4 days during CME storms. Whereas, it shows slower recovery that lasts for more than 6-7 days during CIR-driven storms. We performed detailed study of NO cooling emission owing to the fact that the production of NO depends on the external energy input. The different response of thermospheric NO cooling during CME and CIR storms can be attributed to differences in precipitation of particle (electron and ion) fluxes. A strong correlation with a positive timelag is observed between NO cooling emission and Dst index, coupling functions and particle flux. Further, the correlation between NO cooling flux and particle flux displays a distinct and stronger correlation during CIR storms as compared to CME. This study also shows that Newell coupling function (normalized cross-correlation, r=0.90 for CME and r=0.92 for CIR) and the Akasofu parameter (r=0.92 for CME, r=0.76 for CIR) are better correlated with NO cooling flux, respectively, during CIR- and ICME-driven storms.